(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2026)
This study aims to highlight the importance of sustainability accounting in improving the quality of financial reporting for SK Marble and Granite Company, as a model of Libyan industries receiving governmental support for localization. The significance of the research stems from global transformations in financial disclosure, where traditional reports are no longer sufficient to measure the true performance of institutions, as they lack non-financial indicators that reflect environmental, social, and economic dimensions. Accordingly, the study seeks to fill a knowledge gap in the Libyan context, where previous attention has focused on the banking sector or public companies, while the private industrial sector has remained largely unexplored. The research problem is defined in the main question: To what extent is the application of sustainability accounting important in improving the quality of financial reporting for SK Marble and Granite Company? * This is particularly relevant given the limited local adoption of this approach despite its role in enhancing transparency and credibility. The study employed a descriptive-analytical method, relying on field data collection during the period from August to November 2025, and testing statistical hypotheses linking the three sustainability dimensions (environmental, social, economic) with financial reporting quality according to international disclosure standards such as (GRI). The key findings revealed a statistically significant relationship between sustainable disclosure and financial reporting quality. The environmental dimension contributes to enhancing reliability, the social dimension raises transparency, and the economic dimension strengthens relevance and comparability. Moreover, integrating these dimensions collectively increases investor and local community trust in the company and reduces undesirable accounting practices such as earnings smoothing. The study concludes with several recommendations, most notably: the necessity of obligating private industrial companies in Libya to adopt sustainable disclosure standards, developing local legislation in line with international frameworks, and focusing on training financial staff on environmental, social, and economic accounting requirements. It also recommends integrating sustainability reports within periodic financial reports to enhance transparency and accountability, thereby improving corporate reputation and increasing competitiveness both locally and internationally.